Deep-learning-based surrogate model for fast and accurate simulation in pipeline transport - Qin, Feng; Yan, Zhenghe; Yang, Peng; Tang, Shenglai; Huang, Hu (Frontiers in Energy Research, 2022)
A new deep-learning-based surrogate model is developed and applied for predicting dynamic temperature, pressure, gas rate, oil rate, and water rate with different boundary conditions in pipeline flow. The surrogate model is based on the multilayer perceptron (MLP), batch normalization (BN), and Parametric Rectified Linear Unit (PReLU) techniques. In training, the loss function for data mismatch is considered to optimize the model parameters with means absolute error (MAE). In addition, we also use the dynamic weights, calculated by the input data value, to increase the contribution of smaller inputs and avoid errors caused by large values eating small values in total loss. Finally, the surrogate model is applied to simulate a complex pipeline flow in the eastern part of the South China Sea. We use flow and pressure boundary as the input data in the numerical experiment. A total of 215690 high-fidelity training simulations are performed in the offline stage with commercial software LeadFlow, in which 172552 simulation runs are used for training the surrogate model, which takes about 240 minutes on an RTX2060 GPU. Then the trained model is used to provide pipeline flow forecasts under various boundary conduction. As a result, it is consistent with those obtained from the high-fidelity simulations (e.g., the media of relative error for temperature is 0.56%, pressure is 0.79%, the gas rate is 1.02%, and oil rate is 1.85%, and water is 0.80%, respectively). The online computations from our surrogate model, about 0.008 seconds per run, achieve speedups of over 1250 relative to the high-fidelity simulations, about 10 seconds per run. Overall, this model provides reliable and fast predictions of the dynamic flow along the pipeline.